The Mechanism of Constitutional Lawmaking at the United States of America as an Expression of Law Convergence - Ekaterina A Petrova (RUDN Journal of Law, 2017)
In the article the author analyzes the specificity of the constitutional lawmaking mechanism in the United States in the context of the combination of various lawmaking forms, including those that typical for different legal traditions. The uniqueness of the American legal system is that it combines the features of both common and continental law and so it has integrate nature. The author interprets constitutional lawmaking as the activity of competent lawmaking authorities on creation a constitution as the act of a special kind. The mechanism of constitutional lawmaking covers a system of interrelated elements (the static aspect) and successive stages (the dynamic aspect), providing the establishment and objectification of the constitutional norms in the form of an appropriate constitutional act. Converging nature of the American constitutional lawmaking mechanism has two aspects. The first aspect is connected with the specifics of adoption of the US Constitution. Initially in the mechanism of constitutional lawmaking the instrumentation of a treaty lawmaking has been involved. However the result of it was not an international treaty in the traditional sense, but a normative legal act with the supreme legal force. The second aspect represents a further development of the constitutional provisions through Constitution amendments (which is typical for continental constitutional tradition) and through the judicial constitutional lawmaking which is peculiar for common law tradition. The judicial constitutional lawmaking is carried out through the constitutional doctrines of the U.S. Supreme Court by which the constitutional norms are adopted without formal changes to the varying social conditions. It is concluded that the mechanism of constitutional lawmaking in the United States according to the integration nature of the American legal system expresses the law convergence because it combines three forms of lawmaking technique (contractual, legislative and case-law) and so far provides the best legal result.